Neuroinflammation and Dyskinesia: A Possible Causative Relationship? - Antonella Cardinale; Antonio de Iure; Barbara Picconi (Brain Sciences, 2024)
Levodopa (L-DOPA) treatment represents the gold standard therapy for Parkinson’s disease (PD) patients. L-DOPA therapy shows many side effects, among them, L-DOPA-induced dyskinesias (LIDs) remain the most problematic. Several are the mechanisms underlying these processes: abnormal corticostriatal neurotransmission, pre- and post-synaptic neuronal events, changes in gene expression, and altered plasticity. In recent years, researchers have also suggested non-neuronal mechanisms as a possible cause for LIDs. We reviewed recent clinical and pre-clinical studies on neuroinflammation contribution to LIDs. Microglia and astrocytes seem to play a strategic role in LIDs phenomenon. In particular, their inflammatory response affects neuron-glia communication, synaptic activity and neuroplasticity, contributing to LIDs development. Finally, we describe possible new therapeutic interventions for dyskinesia prevention targeting glia cells.